High Prevalence of Molecular Markers of Plasmodium falciparum Resistance to Sulphadoxine–Pyrimethamine in Parts of Ghana: A Threat to ITPTp-SP? - Afutu, Leslie L.; Boampong, Johnson N; Quashie, Neils B. (Oxford University Press, 2021)
Malaria in pregnancy is a huge public health problem as it is the cause of maternal anaemia, still birth, premature delivery, low birth weight among others. To tackle this problem, WHO recommended the administration, during pregnancy, of intermittent preventive treatment with sulphadoxine–pyrimethamine (IPTp-SP). The introduction of this policy is likely to create SP drug pressure which may lead to the emergence of parasite strains resistant to the drug. This study investigated the prevalence of the molecular markers of SP resistance as pointers to potential failure of IPTp-SP among pregnant women attending antenatal clinic, women at the point of baby delivery and out patients department (OPD) attendees. The study was conducted in health facilities located in parts of Ghana. Prevalence of mutations in dhfr and dhps genes of Plasmodium falciparum was determined using the method described by Duraisingh et al. The outcome of the study indicated the presence of high prevalence of strains of P.falciparum with the resistant alleles of the dhfr or dhps genes in the three categories of participants. There was a high prevalence of triple mutations (IRN) in the dhfr gene of P.falciparum isolates: 71.4% in peripheral blood of antenatal attendees; 74.1% in placenta cord blood of delivering mothers and 71.1% in OPD attendees. Quintuple mutations were only found in 2 (0.5%) isolates from OPD attendees. This observation might have occurred due to the increased use of SP for IPTp among others. There is the need for an interventional measure in order to protect pregnant women and their unborn children
Keywords: Sulphadoxine–pyrimethamine; Mutation; Genotype; Prevalence; Pregnancy; Plasmodium falciparum; Intermittent preventive treatment; WACCBIP